Sun protection behavior beliefs among adults living in rural United States: A qualitative study in Minnesota - Patricia Jewett; Matia Solomon; Katherine Brown; Deveny Flanagan; Emma Kelly; Kelly Kunkel; Megan Schossow; Zora Radosevich; Pamela Mason; Rehana Ahmed; Rebekah Nagler; Carrie Henning-Smith; et al. (PLoS ONE, 2025)
Although skin cancers are considered mostly preventable, more people in the US are diagnosed with skin cancer than all other cancers combined. Sun safety recommendations include wearing sun-protective clothing, a wide-brimmed hat, seeking shade, and using sunscreen. Some evidence exists that sun risk behaviors and skin cancer rates are more frequent among rural than urban US populations, raising questions about underlying factors. We conducted a belief elicitation survey on these four sun protection behaviors among 278 adults (aged 18–60 years) living in rural Minnesota, a state with high sunburn rates and UV-attributable melanoma cases. These qualitative data were analyzed using content analysis, and the identified codes ranked by frequency. Almost all participants emphasized that spending time outside was important to them. The most frequently reported sun protection behaviors were wearing sunscreen and protective clothing. The primary outcomes were obtained from open-ended questions on outcome, normative, and control beliefs associated with each sun protection behavior. While many different beliefs were mentioned, reducing sunburn and skin cancer risk were commonly reported across all behaviors. Beliefs about negative aspects of each behavior (e.g., interference with being physically active or doing work outside, greasy/sticky sunscreen, not getting a suntan, overheating in long clothes or when wearing hats, hats that blow off easily) typically outnumbered positive aspects (e.g., protective behaviors enabling being outside, staying cool in shade, reduced skin aging). The majority of participants believed that most people would approve of all protection behaviors, but many thought that age was a factor for behavior adoption, with young people typically thought to engage less in protective behaviors. Some commonly reported negative aspects of sun protective behaviors were related to activities more common in rural populations, such as working outside. This suggests that rural sun protection promotion may include structural interventions to make sun protection easy, convenient, and accessible without impeding rural lifestyles.